The Murmansk county birth registry (MCBR) : the implementation and applicability of a population-based medical birth registry in the Russian Arctic - Anda, Erik Eik (Universitetet i Tromsø, 2009)
The papers of the thesis are not available in Munin: 1. Anda EE, Nieboer E, Voitov AV, Kovalenko AA, Lapina YM, Voitova EA, Kovalenko LF, Odland JØ: «Implementation, quality control and selected pregnancy outcomes of the Murmansk County Birth Registry (Russia)», Int J Circumpolar Health. 2008; 67(4):318- 34 (publisher's restrictions). Available at http://www.ijch.fi/show_abstract.php?abstract_id=30 2. Anda EE, Nieboer E, Wilsgaard T, Kovalenko AA, and Odland JØ: «Perinatal mortality in relation to birthweight and gestational age: A registry-based comparison for Northern Norway and Murmansk County, Russia» (manuscript) 3. Anda EE, Nieboer E, Dudarev AA, Sandanger TM and Odland JØ: «Intra- and intercompartmental associations between levels of organochlorines in maternal plasma, cord plasma and breast milk, and lead and cadmium in whole blood, for indigenous peoples of Chukotka, Russia», Journal of Environmental Monitoring 2007; 9: 884–93 (Royal Society of Chemistry - publisher's restrictions). Available at http://dx.doi.org/10.1039/b706717h 4. Sandanger TM, Anda EE, Dudarev AA, Nieboer E, Konoplev AV, Vlasov SV, Weber JP Odland JØ and Chashchin VP: «Case study of combining persistent organic pollutants (POPs) datasets in the context of a circumpolar environment-and-health study» (manuscript). Later published with altered title in Science of The Total Environment, Volume 407, Issue 19, 15 September 2009, Pages 5216-5222, available at http://dx.doi.org/10.1016/j.scitotenv.2009.06.020 The Murmansk County Birth Registry (MCBR) was initiated on January 1. 2006. Currently (April 2009) the MCBR has registered over 26 000 births. The registry covers a geographical area known as the Kola Peninsula in Northwest Russia, which is almost entirely located above the Arctic Circle. Murmansk County is about half the size of Norway and had 857 000 inhabitants in 2008. All the 15 delivery departments in the county are involved and their locations stretch from Nikel in the Northwest to Kandalaksha in the south. The Registry Office ...